2010
DOI: 10.5154/r.rchscfa.2010.09.083
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZACIÓN TECNOLÓGICA DE LA MADERA DE Juniperus flaccida VAR. POBLANA MARTÍNEZ

Abstract: El presente estudio se realizó con la finalidad de conocer las características y propiedades tecnológicas de la madera de Juniperus flaccida var. poblana Martínez, para lo cual se utilizó la metodología del Laboratorio de Anatomía y Tecnología de la Madera de la División de Ciencias Forestales de la Universidad Autónoma Chapingo. Las propiedades físicas se determinaron según la norma NOM-EE-167-83 y las mecánicas de acuerdo a las normas ASTM 143-83 en el Campo Experimental San Martinito, del Instituto de Inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…In species richness in both strata and seasons, density and volume are physical characteristics of the wood that determine the presence of different species of cerambycids. This may be because the density of the wood is an intrinsic variable of each plant species and provides special characteristics that are different from each host (Chave et al, 2006; Navarro‐Martínez et al, 2005), so that each species cerambycid has the characteristics that help it degrade different compounds in the hosts with different wood densities.…”
Section: Discussionmentioning
confidence: 99%
“…In species richness in both strata and seasons, density and volume are physical characteristics of the wood that determine the presence of different species of cerambycids. This may be because the density of the wood is an intrinsic variable of each plant species and provides special characteristics that are different from each host (Chave et al, 2006; Navarro‐Martínez et al, 2005), so that each species cerambycid has the characteristics that help it degrade different compounds in the hosts with different wood densities.…”
Section: Discussionmentioning
confidence: 99%
“…De cada probeta se obtuvieron tres láminas de 20 µm de grosor correspondientes a los planos transversal, tangencial y radial. De acuerdo con Navarro-Martínez et al (2005), todas las láminas fueron sumergidas en colorante pardo de Bismarck (Merck) durante cuatro horas, lavadas con agua destilada, deshidratadas con alcohol etílico a 96% durante cinco minutos; posteriormente fueron deshidratadas con alcohol etílico absoluto durante cinco minutos y lubricadas durante 10 segundos con sustituto de xileno Neo-Clear (Merck) antes de ser fijada con el medio de montaje Entellan. Las características anatómicas de las preparaciones fijas fueron observadas a través del microscopio Leica DM3000 (Leica Microsystems) y se describieron conforme a las clasificaciones propuestas por Chattaway (1932), IAWA Committee (19371939) y Wheeler et al (1989).…”
Section: Descripción Anatómicaunclassified
“…Se eligió la probeta más cercana a la corteza de cada una de las rodajas R2 para extraer astillas no mayores a 5 mm × 1 mm × 1 mm, de acuerdo con Navarro-Martínez et al (2005). Las astillas de cada probeta se sumergieron en una solución a partes iguales de peróxido de hidrógeno 29%-32% (MEYER) y ácido acético glacial ACS (Fermont) en un frasco de vidrio.…”
Section: Disociadosunclassified
“…It has been suggested that the specialization and selection in host use arose from a costbenefit balance of physical and/or nutritional factors (Saint-Germain et al, 2007a). Physical characteristics of the wood, such as its density, volume, and decomposition rate depend on the quantity and type of cellular elements that constitute it (Navarro-Martínez et al, 2005) and vary according to species, the zone, and climatic conditions where the trees grow (Rodríguez-Anda et al, 2015). For example, in temperate forests, a higher abundance of cerambycids has been found in wood with low density (0.2-0.5 g/cm 3 ) (Saint-Germain et al, 2007a, 2007b, and in TRF, more cerambycids emerged from wood with low density too (0.4-0.46 g/cm 3 ) (Lanuza-Garay & Barrios, 2018).…”
Section: Introductionmentioning
confidence: 99%